The V6-V1 interpeak interval: a novel criterion for the diagnosis of left bundle branch capture - Jastrzębski, Marek; Burri, Haran; Kiełbasa, Grzegorz; Curila, Karol; Moskal, Paweł; Bednarek, Agnieszka; Rajzer, Marek; Vijayaraman, Pugazhendhi (Europace, 2022)
AIMS: We hypothesized that during left bundle branch (LBB) area pacing, the various possible combinations of direct capture/non-capture of the septal myocardium and the LBB result in distinct patterns of right and left ventricular activation. This could translate into different combinations of R-wave peak time (RWPT) in V1 and V6. Consequently, the V6-V1 interpeak interval could differentiate the three types of LBB area capture: non-selective (ns-)LBB, selective (s-)LBB, and left ventricular septal (LVS). METHODS AND RESULTS: Patients with unquestionable evidence of LBB capture were included. The V6-V1 interpeak interval, V6RWPT, and V1RWPT were compared between different types of LBB area capture. A total of 468 patients from two centres were screened, with 124 patients (239 electrocardiograms) included in the analysis. Loss of LVS capture resulted in an increase in V1RWPT by ≥15 ms but did not impact V6RWPT. Loss of LBB capture resulted in an increase in V6RWPT by ≥15 ms but only minimally influenced V1RWPT. Consequently, the V6-V1 interval was longest during s-LBB capture (62.3 ± 21.4 ms), intermediate during ns-LBB capture (41.3 ± 14.0 ms), and shortest during LVS capture (26.5 ± 8.6 ms). The optimal value of the V6-V1 interval value for the differentiation between ns-LBB and LVS capture was 33 ms (area under the receiver operating characteristic curve of 84.7%). A specificity of 100% for the diagnosis of LBB capture was obtained with a cut-off value of >44 ms. CONCLUSION: The V6-V1 interpeak interval is a promising novel criterion for the diagnosis of LBB area capture.
Keywords: elektrokardiografie; Cardiac Pacing, Artificial; Hisův svazek; Bundle of His; převodní systém srdeční; Heart Conduction System; Humans; lidé; Ventricular Septum; kardiostimulace umělá; mezikomorová přepážka; Electrocardiography